PENDEKATAN KONEKTIVISME DALAM PEMBELAJARAN DI ERA DIGITAL: MEMBANGUN JARINGAN PENGETAHUAN SISWA - Nur Alfilaila (CV. ADIBA AISHA AMIRA, 2026)
The development of information technology in the digital era has brought significant changes in the learning process, from being teacher-centered to student-centered. One relevant approach in addressing these challenges is connectivism, which emphasizes the importance of building knowledge networks through connections between individuals, information sources, and technology. This article aims to analyze the role of the connectivism approach in learning and how this approach can build students' knowledge networks. The method used is a literature study with a descriptive qualitative approach, through the analysis of various relevant scientific sources. The study results show that the implementation of connectivism in learning can improve students' critical thinking skills, collaboration, and digital literacy. In addition, the use of digital platforms such as Google Classroom, YouTube, and WhatsApp has been proven to support the formation of a broader and more dynamic knowledge network. Nevertheless, the implementation of this approach still faces various challenges, such as technological access gaps and low digital literacy. Therefore, support from various parties, especially educators and educational institutions, is needed to optimize the effective and targeted use of technology.